IMPACT OF HALAL SUPPLY CHAIN MANAGEMENT ON THE PRODUCTION PERFORMANCE OF FOOD AND BEVERAGE MSMEs IN CIMAHI CITY - Irdawati, Mutia Ardiani; Dwiana Ratnamurni, Elis (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
The majority of residents in Cimahi City are Muslim, comprising 94.4% of the population. Muslims, whether as buyers or sellers, must ensure that the food available is halal—from the selection of ingredients and the production process to distribution. This study examines the influence of halal supply chain management (HSCM) on the production performance of micro, small, and medium enterprises (MSMEs) in Cimahi City. The research employs a quantitative approach, collecting data through questionnaires distributed to 179 food and beverage MSME respondents in Cimahi City. Multiple linear regression analysis is used as the analytical tool. The findings indicate that halal SCM in purchasing, manufacturing, and distribution positively affects production performance. Furthermore, all three aspects combined have a significant positive impact on production performance. It can be concluded that food and beverage MSMEs in Cimahi City are highly committed to maintaining halal standards by implementing halal supply chain management—from procuring halal materials through the manufacturing process to food distribution. Recommendations include maintaining production performance by applying halal supply chain management and conducting regular evaluations for food and beverage MSME operators to ensure product quality and sustain customer trust.